Covalently anchoring cobalt phthalocyanine on zeolitic imidazolate frameworks for efficient carbon dioxide electroreduction. Issue 9 (26th November 2019) - Yang, Zhongjie; Zhang, Xiaofei; Long, Chang; Yan, Shuhao; Shi, Yanan; Han, Jianyu; Zhang, Jing; An, Pengfei; Chang, Lin; Tang, Zhiyong
Abstract : Transformation of CO2 into fuels has drawn great attention due to increasing carbon emission in recent years. Abstract : Transformation of CO2 into fuels has drawn great attention due to increasing carbon emission in recent years. Coupling metal–organic frameworks (MOFs) with molecular catalysts is a promising technique for boosting the efficiency of carbon dioxide capture and conversion. Herein, a CoTAPc–ZIF-90 hybrid catalyst is synthesized by decorating cobalt phthalocyanine on the outer surface of ZIF-90 through a Schiff base reaction. We demonstrate that the ZIF-90 substrate can cooperate with the cobalt active center to boost the electrocatalytic CO2 reduction performance. CoTAPc–ZIF-90 shows a large current density of 13 mA cm −2 for effective conversion of CO2 into CO in aqueous media at an overpotential of 0.86 V with a faradaic efficiency (FE) of 90%. What's more, the CoTAPc–ZIF-90 hybrid catalyst exhibits significantly higher catalyst stability compared with the free phthalocyanine molecule.